Monoalkoxysilanes and dialkoxysilanes and dense organosilica films made therefrom

JP7637129B2Active Publication Date: 2025-02-27VERSUM MATERIALS US LLC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022516121
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-13
Filing Date
2020-09-11
Publication Date
2025-02-27
Estimated Expiration
2040-09-11

AI Technical Summary

Benefits of technology

【0007】 本明細書において説明される方法及び組成物は、上で説明された1つ又は複数の要求を満たす。モノアルコキシシラン又はジアルコキシシラン前駆体を使用して、約2.80~約3.30のkの値を有する高密度の低k膜を堆積することができる。本発明において説明されるモノアルコキシシラン及びジアルコキシシラン前駆体の両方は、予期されない高い機械特性を有する膜をもたらす一方で、ジアルコキシシラン前駆体は、可能な限り高い機械特性をもたらし、モノアルコキシシラン前駆体は、予期されない高い弾性率/硬度を示し、かつ所与の誘電率の値でプラズマ誘起損傷に対する予期されない高い抵抗性を示すことが期待される膜をもたらす。膜の特性は堆積されたままの膜について観測されたが、後堆積処理、例えばUV硬化を使用して、膜の機械特性をさらに向上することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007637129000008
    Figure 0007637129000008
  • Figure 0007637129000009
    Figure 0007637129000009
  • Figure 0007637129000010
    Figure 0007637129000010
Patent Text Reader

Abstract

1. A method for producing a dense organosilicon film having improved mechanical properties, comprising the steps of: providing a substrate in a reaction chamber; introducing a gaseous composition containing a novel monoalkoxysilane or dialkoxysilane into the reaction chamber; and applying energy to the gaseous composition containing the novel monoalkoxysilane or dialkoxysilane in the reaction chamber to induce a reaction of the gaseous composition containing the novel monoalkoxysilane or dialkoxysilane to deposit an organosilicon film on the substrate, wherein the organosilicon film has a dielectric constant of about 2.8 to about 3.3, an elastic modulus of about 7 to about 30 GPa, and about 10 to about 30 at. % carbon as measured by XPS.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of U.S. Provisional Patent Application No. 62 / 899,807, filed September 13, 2019, the disclosure of which is incorporated herein by reference in its entirety.

[0002] Described herein are compositions and methods for forming dense organosilica dielectric films into films using monoalkoxysilanes or dialkoxysilanes as precursors.More specifically, described herein are compositions and chemical vapor deposition (CVD) methods for forming dense films having a dielectric constant k≧2.7, which films have a high elastic modulus and superior resistance to plasma-induced damage compared to films made from conventional precursors. [Background technology]

[0003] The electronics industry utilizes dielectric materials as insulating layers between circuits and components of integrated circuits (ICs) and related electronic devices. The dimensions of interconnects are being reduced to increase the speed and memory storage capabilities of microelectronic devices (e.g., computer chips). As the dimensions of interconnects are reduced, the insulation requirements for the interlayer dielectric (ILD) are becoming ever more stringent. Shrinking the spacing requires a lower dielectric constant to minimize the RC time constant, where R is the resistance of the conductive interconnect and C is the capacitance of the insulating dielectric interlayer. The capacitance (C) is inversely proportional to the spacing and proportional to the dielectric constant (k) of the interlayer dielectric (ILD). Conventional silica (SiO2) CVD dielectric films made from SiH4 or TEOS (Si(OCH2CH3)4, tetraethyl orthosilicate) and O2 have a dielectric constant k greater than 4.0. There are various approaches that have been attempted in the industry to produce silica-based CVD films with lower dielectric constants, the most successful being the doping of insulating silicon oxide films with organic groups, providing a dielectric constant of about 2.7 to about 3.5. This organosilica glass is typically prepared from an organosilica precursor, such as methylsilane or siloxane, and an oxidizer, such as O2 or NO, to produce dense films (about 1.5 g / cm3). 3 In this specification, organosilica glass is referred to as OSG.

[0004] US 2011 / 10113184 discloses a class of materials that can be used to deposit insulating films with a dielectric constant of about k=2.4 to k=2.8 by a PECVD process. The materials include Si compounds with two hydrocarbon groups that can bond to each other to form a ring structure with the Si atom, or Si compounds with one or more branched hydrocarbon groups. In the branched hydrocarbon group, the C atom bonded to the Si atom, α-C, constitutes a methylene group, and the C atom bonded to the methylene group, β-C, or the C atom bonded to the β-C, γ-C, is the branch point. Specifically, two of the alkyl groups bonded to Si include CH2CH(CH3)CH3, CH2CH(CH3)CH2CH3, CH2CH2CH(CH3)CH3, CH2C(CH3)2CH3, and CH2CH2CH(CH3)2CH3, and the third group bonded to silicon includes OCH3 and OC2H5. The invention claims that a high density of SiCH2Si groups forms via plasma dissociation of alkyl groups R from SiCH2R in the as-deposited films, and the examples in this patent application show that a high density of SiCH2Si groups occurs only after the films are exposed to ultraviolet radiation.The formation of SiCH2Si groups after exposure to UV radiation has been reported in the literature (Grill, A. “PECVD low and Ultralow Dielectric Constant Materials: From Invention and Research to Products”, J.Vac.Sci.Technol.B, 2016, 34, 020801-1 - 020801-4; Baklanov, MR et al. “Plasma Processing of Low-k Dielectrics”, J.Appl.Phys., 2013, 113, 041101-1 - 041101-41; Priyadarshini, D.; Nguyen, SV; Shobha, H.; Liniger, E., Chen, JH-C.; Huang, H.; Cohen, SA; Grill, A. “Advanced Single Precursor Based pSiOCH k=2.4 for ULSI Interconnects” J. Vac. Sci. Technol. B, 2017, 35, 021201-021201-6).

[0005] There are various other drawbacks to the approach disclosed in US2011 / 10113184. The first is the need for large alkyl groups, including branched alkyl groups, in the precursor structure. These molecules are costly to synthesize and typically have high boiling points and low volatility due to their inherently high molecular weight. High boiling points and low volatility make it difficult to efficiently transport such molecules in the gas phase, as required for PECVD processes. Perhaps most importantly, the dielectric constant values ​​reported in this approach are low, below 2.8. It is generally accepted that the minimum achievable dielectric constant for dense low-k films with reasonable mechanical properties is roughly 2.7-2.8. Thus, the approach disclosed in US2011 / 10113184 is not directed to the deposition of dense low-k films without post-deposition processing (i.e., UV curing), but is more similar to the linked porogen approach to generate porous low-k films. Summary of the Invention [Problem to be solved by the invention]

[0006] Plasma or process induced damage (PID) in low-k films is caused by the removal of carbon from the film during plasma exposure, especially during etching and photoresist stripping processes. Carbon depletion in low-k films can cause one or more of the following problems: increase in the dielectric constant of the film; etching of the film and bowing of features during wet cleaning steps (i.e., contour erosion); water absorption into the film due to loss of hydrophobicity; pattern collapse of fine features during wet cleaning steps after pattern etching; and / or integration problems when depositing subsequent layers, such as, but not limited to, copper diffusion barriers, e.g., Ta / TaN, advanced Co or MnN barrier layers. Thus, process induced damage in low-k films is a key issue that device manufacturers must resolve when incorporating low-k materials in ULSI interconnects. Films with improved mechanical properties (high modulus, high hardness) reduce line edge roughness in patterned features, reduce pattern collapse, and lead to greater internal mechanical stresses in interconnects, reducing defects due to electromigration. Thus, there is a need for low-k films that have strong resistance to PID and the highest possible mechanical properties for a given dielectric constant. Furthermore, there is a need to deposit these films without the need for post-deposition treatments such as UV curing, since UV curing reduces throughput in a high volume manufacturing environment, adds cost and complexity to the process, reduces the carbon content of the film (increasing the depth of PID), and increases the porosity of the film (increasing the depth of PID). That is, the properties of the as-deposited film should be acceptable without the need for post-deposition treatments such as UV curing. [Means for solving the problem]

[0007] The methods and compositions described herein meet one or more of the requirements described above. Using monoalkoxysilane or dialkoxysilane precursors, dense low-k films can be deposited with k values ​​of about 2.80 to about 3.30. While both monoalkoxysilane and dialkoxysilane precursors described in the present invention result in films with unexpectedly high mechanical properties, the dialkoxysilane precursors result in films that are expected to exhibit unexpectedly high elastic modulus / hardness and unexpectedly high resistance to plasma-induced damage at a given value of dielectric constant. Although the film properties were observed for the as-deposited films, post-deposition treatments, such as UV curing, can be used to further improve the mechanical properties of the films.

[0008] In one aspect, the present disclosure provides a method for producing dense organosilica films (or low-k films) with improved mechanical properties, comprising: Providing a substrate in a reaction chamber; Formulas (I) and (2): (1)HR 1 R 2 SiOR 3 (In the formula, R 1 is methyl, and R 2 Branched or cyclic C3-C 10 alkyl, preferably iso-propyl, sec-butyl or tert-butyl; R 3 is linear, branched or cyclic C1-C 10 alkyl, preferably selected from methyl, ethyl, propyl, iso-propyl, butyl, sec-butyl, iso-butyl or tert-butyl (2)R 4 R 5 Si(OR 6 )2 (In the formula, R 4 is hydrogen or methyl, R 5 is linear, branched or cyclic C1-C 10alkyl, preferably iso-propyl or tert-butyl; R 6 Linear, branched or cyclic C3-C 10 alkyl, preferably selected from propyl, iso-propyl, butyl, sec-butyl, iso-butyl or tert-butyl (wherein for the above formula, the combination of alkyl groups is selected such that the boiling point of the molecule is less than 200° C., and additionally, for optimal performance, the R groups can be selected to form secondary or tertiary radicals upon homolytic bond dissociation (e.g., SiO-R→SiO·+R· or Si-R→Si·+R·, where R is a secondary or tertiary radical, such as an isopropyl radical, a sec-butyl radical, or a tert-butyl radical); and applying energy to a gaseous reaction composition comprising a monoalkoxysilane or a dialkoxysilane in the reaction chamber to induce reaction of the gaseous composition comprising a monoalkoxysilane or a dialkoxysilane to deposit an organosilicon film on the substrate. wherein the organosilica film has a dielectric constant of about 2.8 to about 3.3 and an elastic modulus of about 7 to about 30 GPa.

[0009] In another aspect, the present disclosure provides a method for producing dense organosilica films having improved mechanical properties, comprising: Providing a substrate in a reaction chamber; introducing a gaseous composition comprising a monoalkoxysilane or a dialkoxysilane into the reaction chamber; and applying energy to the gaseous reaction composition comprising the monoalkoxysilane or dialkoxysilane in the reaction chamber to induce reaction of the gaseous composition comprising the monoalkoxysilane or dialkoxysilane to deposit an organosilica film on the substrate. wherein the organosilica film has a dielectric constant of about 2.8 to about 3.3, an elastic modulus of about 7 to about 30 GPa, and about 10 to about 30 at % carbon as measured by XPS. [Brief description of the drawings]

[0010] [Figure 1] 1 is a graph depicting the relationship between the percentage of Si-Me groups in a thin film and mechanical strength. [Diagram 2] 1 is a chart depicting IR spectra for low-k (3.1) films deposited using dimethyl-di-iso-propoxysilane (DMDIPOS), iso-propyl-methyl-ethoxysilane (IPMEOS), and dimethyl-dimethoxysilane (DMDMOS). [Diagram 3] 1 is a graph depicting the relationship of elastic modulus for dense dimethyl-di-iso-propoxysilane and dimethyl-dimethoxysilane films having different dielectric constants. [Figure 4] 1 is a graph depicting the relationship between the density of Si(CH3) groups for high density dimethyl-di-iso-propoxysilane and dimethyl-dimethoxysilane films having different dielectric constants. [Diagram 5] FIG. 1 is a graph depicting terminal silicon methyl density (Si(CH3)x), as measured by infrared spectroscopy, plotted against hardness for dense k=3.1 films deposited using dimethyl-di-iso-propoxysilane, iso-propyl-methyl-ethoxysilane, diethoxy-methylsilane, and dimethyl-dimethoxysilane. [Figure 6] 1 is a graph depicting the relationship between the density of SiCH2Si groups for dense films having different dielectric constants deposited using iso-propyl-methyl-ethoxysilane and diethoxy-methylsilane. [Figure 7] 1 is a GC-MS chromatogram for iso-propyl-methyl-ethoxysilane synthesized according to Example 1. [Figure 8] GC-MS chromatogram for iso-propyl-methyl-iso-propoxysilane synthesized according to Example 2. [Figure 9] 1 is a GC-MS chromatogram for di-iso-propoxydimethylsilane synthesized according to Example 3. [Figure 10] 1 is a GC-MS chromatogram for di-sec-butoxydimethylsilane synthesized according to Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] 1. A chemical vapor deposition method for producing dense organosilica films having improved mechanical properties, comprising: Providing a substrate in a reaction chamber; introducing a gaseous composition comprising a monoalkoxysilane or a dialkoxysilane, a gaseous oxidant such as O2 or N2O, and an inert gas such as He into a reaction chamber; and applying energy to the gaseous composition comprising the monoalkoxysilane or dialkoxysilane in the reaction chamber to induce a reaction of the gaseous composition comprising the monoalkoxysilane or dialkoxysilane to deposit an organosilica film on the substrate. and wherein the organosilica film has a dielectric constant of about 2.7 to about 3.3, an elastic modulus of about 7 to about 30 GPa, and about 10 to about 30 at. % carbon as measured by XPS, preferably a dielectric constant of about 2.9 to about 3.2, an elastic modulus of about 9 to about 30 GPa, and about 10 to about 25 at. % carbon as measured by XPS.

[0012] Further provided is a method for producing dense organosilica films having improved mechanical properties, comprising the steps of: Providing a substrate in a reaction chamber; introducing a gaseous composition comprising a monoalkoxysilane or a dialkoxysilane, a gaseous oxidant such as O2 or N2O, and an inert gas such as He into a reaction chamber; and applying energy to a gaseous composition comprising a monoalkoxysilane or a dialkoxysilane to deposit an organosilica film on a substrate; wherein the organosilica film has a dielectric constant of about 3.0 to about 3.2 and an elastic modulus of about 12 to about 30 GPa.

[0013] The monoalkoxysilane or dialkoxysilane compounds described in the present invention provide unique properties that allow them to exhibit surprisingly unexpected high mechanical properties and achieve high density organosilica films at a given dielectric constant value of about 2.7 to about 3.3, compared to prior art structure-forming precursors, such as diethoxymethylsilane (DEMS®) and dimethoxy-dimethylsilane (DMDMOS). Without being bound by theory, it is believed that the monoalkoxysilane or dialkoxysilane described in the present invention can provide stable radicals, such as (CH3)2CH· and (CH3)3C·, during plasma-enhanced chemical vapor deposition. Such radicals are more stable than the methyl radicals disclosed in the prior art, such as Me3SiOMe or Me3SiOEt (Bayer, C. et al., “Overall Kinetics of SiOx Remote-PECVD using Different Organosilicon Monomers”, 116-119, Surf.Coat.Technol., 874, (1999)). A higher density of stable radicals in the plasma, such as (CH3)2CH· and (CH3)3C·, increases the likelihood of reaction with the terminal silicon methyl groups in the compound of formula (1) or the compound of formula (2). This reduces the density of terminal silicon methyl groups in the film, resulting in higher mechanical properties. It is recognized that a higher density of stable radicals in the plasma can be achieved when the alkyl group bonded directly to the silicon atom is selected from branched or cyclic alkyls, such as isopropyl, sec-butyl, t-butyl, or cyclohexyl.

[0014] It is well known in organic chemistry that more energy must be supplied to generate a primary carbon radical (e.g., the ethyl radical CH3CH2·) than a secondary carbon radical (e.g., the isopropyl radical (CH3)2CH·). This is due to the higher stability of the isopropyl radical with respect to the ethyl radical. The same principle applies to the homolytic bond dissociation of oxygen-carbon bonds in silicon alkoxy groups; it requires less energy to dissociate the oxygen-carbon bond in isopropoxysilane than in ethoxysilane. Similarly, it requires less energy to dissociate the silicon-carbon bond in isopropylsilane than in ethylsilane. Without being bound by theory, it is speculated that bonds that require less energy to break are more likely to dissociate in a plasma. Thus, the Si-OPr i , Si-OBu s or Si-OBu t Monoalkoxysilanes or dialkoxysilanes bearing the Si-OMe group can provide a higher density of SiO radicals in the plasma compared to those bearing the Si-OMe group. i , Si-Bu s or Si-Bu t Monoalkoxysilanes or dialkoxysilanes bearing the Si-O-Me group can provide a higher density of Si·-type radicals in plasma compared to those bearing only Si-Me groups. Presumably, this is due to the fact that Si-O-Pr i , Si-OBu s or Si-OBu t This, in turn, presumably contributes to the differentiated properties of films deposited using monoalkoxysilanes or dialkoxysilanes having Si-OMe groups versus those having Si-Pr groups. i , Si-Bu s or Si-Bu tThis contributes to the differentiated properties of films deposited using monoalkoxysilanes or dialkoxysilanes having Si-Me groups versus films deposited using monoalkoxysilanes or dialkoxysilanes having Si-Me groups.

[0015] Some of the advantages over the prior art achieved by monoalkoxysilanes or dialkoxysilanes as silicon precursors include, but are not limited to, higher mechanical properties, lower cost, ease of synthesis, and, in the case of monoalkoxysilanes, higher disilylmethylene (SiCHSi) density.

[0016] The table below lists selected monoalkoxysilanes or dialkoxysilanes having formula 1 or 2. The most preferred molecules are those with a combination of alkyl groups selected such that the boiling point of the molecule is less than 200° C. (preferably less than 150° C.). Additionally, for optimal performance, the alkoxy groups form secondary or tertiary radicals upon homolytic bond dissociation (e.g., Si-R 2 →Si +R 2 or SiO-R 3 →SiO +R 3 , where R 2 · and R 3 is a secondary or tertiary radical, for example an isopropyl radical or a tert-butyl radical. Furthermore, the most preferred monoalkoxysilanes or dialkoxysilanes according to the present invention are those in which R 1 , R 2 , R 4 or R 5 It contains at least one methyl group.

[0017] List of exemplary monoalkoxysilanes or dialkoxysilanes having formula 1 or 2 [Table 1-1] [Table 1-2]

Table 1-3

[0018] Preferably, the monoalkoxysilane or dialkoxysilane having formula 1 or 2 according to the present invention and the composition comprising the monoalkoxysilane or dialkoxysilane compound having formula 1 or 2 according to the present invention are substantially free of halide ions.As used herein, the term "substantially free" means that when referring to halide ions (or halides), such as chloride (i.e. chloride-containing species, such as HCl or silicon compounds having at least one Si-Cl bond, such as Me2HSiCl), fluoride, bromide and iodide, the amount is less than 50 ppm (by weight) as measured by ion chromatography (IC), less than 10 ppm (by weight) as measured by ion chromatography (IC), less than 5 ppm (by weight) as measured by ion chromatography (IC), preferably less than 3 ppm as measured by IC, more preferably less than 1 ppm as measured by IC, and most preferably 0 ppm as measured by IC.Chloride is known to act as a decomposition catalyst for silicon precursor compounds having formula 1 or 2. Significant levels of chloride in the final product may cause the silicon precursor compound to decompose. Slow decomposition of the silicon precursor compound may directly affect the film deposition process, making it difficult for semiconductor manufacturers to meet film specifications. In addition, shelf life or stability is negatively affected by the faster decomposition rate of the silicon precursor compound, thereby making it difficult to guarantee a shelf life of 1-2 years. Accelerated decomposition of the silicon precursor compound thus leads to safety and performance concerns regarding the formation of these flammable and / or pyrophoric gaseous by-products. Preferably, the monoalkoxysilane or dialkoxysilane having formula 1 or 2 is substantially free of metal or metals, such as Li, Na, K, Mg, Ca, Al, Fe, Ni, Cr. As used herein, the term "substantially free" when referring to such metal or metals means less than 5 ppm (by weight), preferably less than 3 ppm, more preferably less than 1 ppm, and most preferably less than 0.1 ppm, as measured by ICP-MS.In some embodiments, the silicon precursor compound having formula 1 and 2 does not contain metal or metals, such as Li, Na, K, Mg, Ca, Al, Fe, Ni, Cr. As used herein, the term "free of metal impurities" means less than 1 ppm (by weight), preferably less than 0.1 ppm, when measured by ICP-MS or other analytical methods for measuring metals, when referring to Li, Na, K, Mg, Ca, Al, Fe, Ni, Cr. Preferably, the monoalkoxysilane or dialkoxysilane having formula 1 or 2 also does not substantially contain water. As used herein, the term "substantially free" means less than 10 ppm (by weight), preferably less than 5 ppm, more preferably less than 3 ppm, most preferably less than 0.1 ppm, when measured by Karl Fischer titration or ICP-MS, when referring to water content. Additionally, preferably, the monoalkoxysilanes having Formula 1 or 2, when used as precursors for depositing organosilica glass ("OSG") films, have a purity of 98 wt% or greater, more preferably 99 wt% or greater, as measured by GC.

[0019] Low-k dielectric films are organo-silica glass ("OSG") films or materials. Organosilicates are used in the electronics industry, for example, as low-k materials. The material properties depend on the chemical composition and structure of the film. Since the type of organosilicon precursor has a strong effect on the structure and composition of the film, it is beneficial to use a precursor that provides the required film properties to ensure that the addition of the amount of porosity required to reach the desired dielectric constant does not produce a mechanically unsound film. The methods and compositions described herein provide the desired balance of electrical and mechanical properties, as well as other beneficial film properties, such as sufficient total carbon content and carbon type (Si(CH3) x The present invention provides a means for producing low-k dielectric films having a dielectric constant of 100 kV or less (e.g., SiCH2Si) to provide improved integrated plasma resistance.

[0020] In certain embodiments of the methods and compositions described herein, a layer of silicon-containing dielectric material is deposited on at least a portion of a substrate through a chemical vapor deposition (CVD) process using a reaction chamber.Accordingly, the method includes providing a substrate in a reaction chamber.Suitable substrates include, but are not limited to, semiconductor materials such as gallium arsenide ("GaAs"), silicon, and silicon-containing compositions such as crystalline silicon, polysilicon, amorphous silicon, epitaxial silicon, silicon dioxide ("SiO2"), silicon glass, silicon nitride, fused silica, glass, quartz, borosilicate glass, and combinations thereof.Other suitable materials include chromium, molybdenum, tungsten, cobalt, copper, metal alloys, and other metals commonly used in semiconductor, integrated circuit, flat panel display, and flexible display applications. The substrate may have further layers such as silicon, SiO2, organosilicate glass (OSG), fluorinated silicate glass (FSG), boron carbonitride, silicon carbide, hydrogenated silicon carbide, silicon nitride, hydrogenated silicon nitride, silicon carbonitride, hydrogenated silicon carbonitride, boron nitride, organic-inorganic composites, photoresists, organic polymers, porous organic and inorganic materials and composites, metal oxides such as aluminum oxide and germanium oxide. Additionally, further layers may be germanosilicates, aluminosilicates, copper, cobalt and aluminum, and diffusion barrier materials such as, but not limited to, TiN, Ti(C)N, TaN, Ta(C)N, Ta, W, or WN.

[0021] Typically, the reaction chamber is, for example, a thermal CVD or plasma enhanced CVD reactor, or a batch furnace type reactor in various methods. In one embodiment, a liquid transport system can be utilized. In the liquid transport formulation, the precursor described herein can be transported in undiluted liquid form, or alternatively, can be used in a solvent formulation or composition that includes the precursor described herein. Thus, in certain embodiments, the precursor formulation can include one or more solvent components of suitable characteristics that may be desired and advantageous for forming a film on a substrate in a given end use application.

[0022] The method disclosed herein comprises introducing a gaseous composition comprising monoalkoxysilane or dialkoxysilane into a reaction chamber.In some embodiments, the composition may comprise additional reactants, such as oxygen-containing species, such as O2, O3 and N2O, gaseous or liquid organic substances, CO2 or CO.In one particular embodiment, the reaction mixture introduced into the reaction chamber comprises at least one oxidizing agent selected from the group consisting of O2, N2O, NO, NO2, CO2, water, H2O2, ozone and combinations thereof.In an alternative embodiment, the reaction mixture does not comprise an oxidizing agent.

[0023] The compositions for depositing dielectric films described herein include from about 40 to about 100 wt % of a monoalkoxysilane or a dialkoxysilane.

[0024] In embodiments, gaseous compositions containing monoalkoxysilanes or dialkoxysilanes can be used in conjunction with curing additives to further increase the elastic modulus of the as-deposited films.

[0025] In some embodiments, the gaseous composition comprising the monoalkoxysilane or dialkoxysilane is substantially free or free of halides, such as chloride.

[0026] In addition to the monoalkoxysilane or dialkoxysilane, additional materials can be introduced into the reaction chamber before, during, and / or after the deposition reaction. Such materials include, for example, inert gases (e.g., He, Ar, N2, Kr, Xe, etc., which can be used as carrier gases for less volatile precursors and / or can promote curing of the as-deposited material to provide a more stable final film).

[0027] Any reagents used, including monoalkoxysilanes or dialkoxysilanes, can be transported into the reactor separately from another source or as a mixture. The reagents can be transported into the reactor system by any of a number of means, preferably using a pressurizable stainless steel vessel equipped with a suitable valve that allows the transport of liquids into the process reactor. Preferably, the precursors are transported into the process vacuum chamber as gases, i.e., the liquids must be vaporized before being transported into the process chamber.

[0028] The method disclosed herein includes applying energy to a gaseous composition comprising a monoalkoxysilane or dialkoxysilane in a reaction chamber to induce reaction of the gaseous composition comprising a monoalkoxysilane or dialkoxysilane to deposit an organosilica film on a substrate, the organosilica film having a dielectric constant of about 2.8 to about 3.3 in some embodiments, 2.90 to 3.3 in other embodiments, and 3.0 to 3.2 in more preferred embodiments, an elastic modulus of about 7 to about 30 GPa, preferably 10 to 30 GPa, and about 10 to about 30 at% carbon as measured by XPS. Energy is applied to the gaseous reagent to induce the monoalkoxysilane or dialkoxysilane, and other reactants, if present, to react to form a film on the substrate. Such energy can be provided, for example, by plasma, pulsed plasma, helicon plasma, high density plasma, inductively coupled plasma, remote plasma, hot filament, and thermal (i.e., non-filament) methods. A secondary rf frequency source can be used to modify the plasma characteristics at the substrate surface. Preferably, the film is formed by plasma enhanced chemical vapor deposition ("PECVD").

[0029] Preferably, the flow rates for each of the gaseous reagents are between 10 and 5000 sccm, more preferably between 30 and 3000 sccm, for a single 300 mm wafer. The actual flow rates required may depend on the size of the wafer and the configuration of the chamber, and are in no way limited to 300 mm wafers or single wafer chambers.

[0030] In certain embodiments, the film is deposited at a deposition rate of about 5 to about 700 nanometers (nm) per minute, hi other embodiments, the film is deposited at a deposition rate of about 30 to 200 nanometers (nm) per minute.

[0031] Typically, the pressure in the reaction chamber during deposition is from about 0.01 to about 600 torr, or from about 1 to about 15 torr.

[0032] Preferably, films are deposited to a thickness of 0.001 to 500 microns, although thickness can vary as required. Blanket films deposited on unpatterned surfaces have excellent uniformity with less than 3% / 1 standard deviation thickness variation across the substrate, with reasonable edge exclusion (e.g., the outermost 5 mm edge of the substrate is not included in statistical calculations of uniformity).

[0033] In addition to the OSG products of the invention, the invention includes processes for making the products, methods for using the products, and compounds and compositions useful for preparing the products. For example, a process for producing integrated circuits on semiconductor devices is disclosed in U.S. Patent No. 6,583,049, which is incorporated herein by reference.

[0034] Dense organosilica films produced by the disclosed methods, especially those produced using monoalkoxysilane compounds of formula (1) as low-k precursors, exhibit good resistance to plasma-induced damage, especially during etching and photoresist stripping processes.

[0035] Dense organosilica films produced by the disclosed methods exhibit superior mechanical properties for a given dielectric constant compared to dense organosilica films having the same dielectric constant but made from commercially available prior art structure-forming precursors such as diethoxymethylsilane (DEMS®) and dimethoxy-dimethylsilane (DMDMOS). Typically, the resulting (as-deposited) organosilica films have a dielectric constant of about 2.80 to about 3.30 in some embodiments, about 2.90 to about 3.20 in other embodiments, and about 3.0 to about 3.2 in still other embodiments, an elastic modulus of about 7 to about 30 GPa, and about 10 to about 30 at% carbon as measured by XPS.

[0036] The resulting dense organosilica films may be subjected to post-treatment processes after they have been deposited. Thus, as used herein, the term "post-treatment" means treating the film with energy (e.g., heat, plasma, photons, electrons, microwaves, etc.) or chemicals to further enhance the properties of the material.

[0037] The conditions under which the post-treatment is carried out can vary widely, for example, the post-treatment may be carried out under high pressure or under a vacuum atmosphere.

[0038] UV annealing is the preferred method, carried out under the following conditions:

[0039] The environment may be inert (e.g., nitrogen, CO2, noble gases (He, Ar, Ne, Kr, Xe), etc.), oxidizing (e.g., oxygen, air, oxygen-lean environment, oxygen-enriched environment, ozone, nitrous oxide, etc.), or reducing (dilute or concentrated hydrogen, hydrocarbons (saturated, unsaturated, straight or branched chain, aromatic), etc.). Preferably, the pressure is from about 1 Torr to about 1000 Torr. However, for thermal annealing as well as any other post-processing means, a vacuum atmosphere is preferred. Preferably, the temperature is from 200 to 500°C, with a temperature ramp rate of 0.1 to 100°C / min. Preferably, the total UV annealing time is from 0.01 min to 12 h.

[0040] The present invention will be illustrated in more detail with reference to the following examples, which should not be understood as being limited thereto. It is also recognized that the precursors described in this invention can be used to deposit porous low-k films with similar process advantages to existing porous low-k films (i.e., higher resistance to plasma-induced damage for a given value of dielectric constant, and higher elastic modulus). EXAMPLES

[0041] Example 1: Synthesis of iso-propyl-methyl-ethoxysilane (IPMEOS) 229.0 g (1.70 mol) of diethoxymethylsilane and 1 L of hexane were charged to a three-necked round-bottom flask equipped with a thermocouple and a condenser. 853 mL (1.70 mol) of 2 M isopropylmagnesium chloride in THF was added dropwise to slowly raise the temperature of the reaction mixture to 35° C. The resulting grey slurry was cooled back to room temperature with stirring. The magnesium salts were filtered from the reaction mixture. After removal of the solvent by distillation, fractional distillation collected 148 g of isopropyl-methyl-ethoxysilane. The yield was 66%. Figure 7 shows the GC-MS chromatogram for the synthesized isopropyl-methyl-ethoxysilane.

[0042] Example 2: Synthesis of iso-propyl-methyl-iso-propoxysilane 3.4 mL (6.84 mmol) of 2.0 M iso-propylmagnesium chloride in THF was added dropwise to 1.11 g (6.84 mmol) of di-iso-propoxy-methylsilane in hexane at room temperature. The salt precipitated immediately and the reaction was slightly exothermic. After 2 hours of stirring, the salt was allowed to settle to the bottom of the vial. Figure 8 is a GC-MS chromatogram for the synthesized iso-propyl-methyl-iso-propoxy-silane.

[0043] Example 3: Synthesis of di-iso-propoxydimethylsilane 380 g (6.31 mol) of isopropyl alcohol was added dropwise to 327 g (2.53 mol) of dichlorodimethylsilane in 500 mL of hexane at reflux. A nitrogen purge was introduced to purge the HCl. After the addition was complete, reflux was continued for 1 hour, and then the reaction was allowed to cool to room temperature. 30 mL of iso-propylamine was added to drive the reaction to completion. After removing the iso-propylamine hydrochloride by filtration, the crude product was fractionally distilled at 88° C. and 180 Torr. 392 g of di-iso-propoxydimethylsilane was obtained with a purity of 99.8%. The yield was 86%. Figure 9 is a GC-MS chromatogram for the synthesized di-iso-propoxydimethylsilane.

[0044] Example 4: Synthesis of di-sec-butoxydimethylsilane 646.0 g (8.72 mol) of 2-butanol was added dropwise to 500.0 g (3.87 mol) of dichlorodimethylsilane in 500 mL of hexane at reflux. A nitrogen purge was introduced to purge the HCl. After the addition was complete, reflux was continued for 1 hour and then the reaction was allowed to cool to room temperature. 162 mL of iso-propylamine was added to drive the reaction to completion. The resulting reaction slurry was filtered and the solvent was removed by distillation at atmospheric pressure. Vacuum distillation at 50° C. / 6 mmHg produced 695.6 g of di-sec-butoxydimethylsilane with a purity of 99.2%. The yield was 88%. FIG. 10 is a GC-MS chromatogram for the synthesized di-sec-butoxydimethylsilane.

[0045] Examples 5-8: Synthesis of additional dialkoxysilanes having formula 2 Additional dialkoxysilanes were prepared in a manner similar to that of Example 4 and characterized by GC-MS. The molecular weight (MW), structure, and corresponding major MS fragmentation peaks of each compound are provided below to confirm their identity. [Table 2]

[0046] All deposition experiments, including the comparative experiments, were performed on a 300 mm AMAT Producer® SE depositing films on two wafers simultaneously. The precursor and gas flow rates therefore correspond to the flow rates required to deposit films on two wafers simultaneously. The listed RF power per wafer is correct when each wafer processing station has its own independent RF power supply. The listed deposition pressure is correct when both wafer processing stations are held at the same pressure. The Producer® SE was equipped with a Producer® Nanocure chamber used to UV cure certain films after the deposition process was completed.

[0047] Although illustrated and described above with reference to certain specific embodiments and examples, the present invention is nevertheless not intended to be limited to the details shown. Rather, various changes in details can be made within the scope of the equivalents of the claims and without departing from the spirit of the present invention. For example, all ranges broadly described in this document are expressly intended to include within their scope all narrower ranges that are within that broad range. It is recognized that the compounds disclosed in formula (1) or formula (2) in the present invention can also be used as structure-forming agents for the deposition of porous low-k films with high elastic modulus, high XPS carbon content, and high resistance to plasma-induced damage.

[0048] The thickness and refractive index were measured on a Woollam Model M2000 spectroscopic ellipsometer. The dielectric constant was determined using the Hg probe technique on medium resistivity p-type wafers (8-12 Ω·cm). FTIR spectra were measured using a Thermo Fisher Scientific Model iS50 spectrometer equipped with a nitrogen purged Pike Technologies Map300 for processing 12-inch wafers. FTIR spectra were used to determine the relative density of bridging disilylmethylene groups in the films, or the concentration of terminal silicon methyl groups (Si-Me or Si(CH3) x The relative density of terminal silicon methyl groups (i.e., Si-Me or Si(CH3)) in the films was calculated, as determined by infrared spectroscopy. x The density of -1 Si(CH3) with the center at x The area of ​​the infrared band is approximately 1250 cm -1 ~920cm -1 SiO x The relative density of bridging disilylmethylene groups in the film (i.e., the density of SiCH2Si) is defined as 100 times the area of ​​the band, as determined by infrared spectroscopy. -1 The area of ​​the SiCH2Si infrared band centered around 1250 cm -1 ~920cm -1 SiOx It is defined as 10000 times divided by the area of ​​the band. Mechanical properties were determined using a KLA iNano nanoindenter.

[0049] Compositional data was obtained by X-ray photoelectron spectroscopy (XPS) on either a PHI 5600 (73560, 73808) or a Thermo K-Alpha (73846) and is provided in atomic weight percent. The atomic weight percent (%) values ​​reported in the tables do not include hydrogen.

[0050] For each precursor in the examples listed below, deposition conditions were optimized to produce films with high mechanical properties at a dielectric constant of 3.1 or 3.2.

[0051] Comparative Example 1: Deposition of Dense, Diethoxymethylsilane (DEMS®)-Based Films Dense, DEMS®-based films were deposited using the following process conditions for a 300 mm process: DEMS® precursor was delivered to the reaction chamber via direct liquid injection (DLI) at a flow rate of 750 mg / min using a He carrier gas flow of 1500 sccm, and a 300 watt, 13.56 MHz plasma was applied at a chamber pressure of 10 Torr, at a sill temperature of 345° C., with a showerhead / heated sill spacing of 380 mils. Various properties of the as-deposited films, such as dielectric constant (k), elastic modulus, hardness, density of various functional groups as determined by infrared spectroscopy, and atomic composition by XPS, were obtained as described above and are provided in Table 2.

[0052] Comparative Example 2: Deposition of dense, dimethyl-dimethoxysilane (DMDMOS)-based films Dense, DMDMOS-based films were deposited using the following process conditions for a 300 mm process: DMDMOS precursor was delivered to the reaction chamber via direct liquid injection (DLI) at a flow rate of 1500 mg / min using a He carrier gas flow of 1500 sccm, and a 376 watt 13.56 MHz plasma was applied at a chamber pressure of 7.5 Torr, with a showerhead / heated pedestal spacing of 380 mils, a pedestal temperature of 350° C., and an O2 flow rate of 25 sccm. Various properties of the as-deposited films, such as dielectric constant (k), elastic modulus, hardness, and density of various functional groups as determined by infrared spectroscopy, were obtained as described above and are provided in Table 1.

[0053] Comparative Example 3: Deposition of dense, dimethyl-dimethoxysilane (DMDMOS)-based films Dense, DMDMOS-based films were deposited using the following process conditions for a 300 mm process: DMDMOS precursor was delivered to the reaction chamber via direct liquid injection (DLI) at a flow rate of 2000 mg / min using a He carrier gas flow of 1500 sccm, and a 430 watt 13.56 MHz plasma was applied at a chamber pressure of 7.5 Torr, with a showerhead / heated pedestal spacing of 380 mils, a pedestal temperature of 350° C., and an O2 flow rate of 25 sccm. Various properties of the as-deposited films, such as dielectric constant (k), elastic modulus, hardness, density of various functional groups as determined by infrared spectroscopy, and atomic composition by XPS, were obtained as described above and are provided in Table 2.

[0054] Example 9: Deposition of dense, dimethyl-di-iso-propoxysilane (DMDIPOS)-based films Dense, DMDIPOS-based films were deposited using the following process conditions for a 300 mm process: DMDIPOS precursor was delivered to the reaction chamber via direct liquid injection (DLI) at a flow rate of 700 mg / min using a He carrier gas flow of 925 sccm, and a 425 watt 13.56 MHz plasma was applied at a chamber pressure of 6.25 Torr, with a showerhead / heated platform spacing of 380 mils, a platform temperature of 350° C., and an O2 flow rate of 20 sccm. Various properties of the as-deposited films, such as dielectric constant (k), elastic modulus, hardness, density of various functional groups as determined by infrared spectroscopy, and atomic composition by XPS, were obtained as described above and are provided in Table 1.

[0055] Example 10: Deposition of dense, dimethyl-di-iso-propoxysilane (DMDIPOS)-based films Dense, DMDIPOS-based films were deposited using the following process conditions for a 300 mm process: DMDIPOS precursor was delivered to the reaction chamber via direct liquid injection (DLI) at a flow rate of 800 mg / min using a He carrier gas flow of 925 sccm, and a 200 watt 13.56 MHz plasma was applied at a chamber pressure of 7.0 Torr, with a showerhead / heated platform spacing of 380 mils inches, a platform temperature of 400° C., and an O2 flow rate of 8 sccm. Various properties of the as-deposited films, such as dielectric constant (k), elastic modulus, hardness, density of various functional groups as determined by infrared spectroscopy, and atomic composition by XPS, were obtained as described above and are provided in Table 2.

[0056] Example 11: Deposition of dense, iso-propyl-methyl-ethoxysilane (IPMEOS)-based films Dense, IPMEOS-based films were deposited using the following process conditions for a 300 mm process: IPMEOS precursor was delivered to the reaction chamber via direct liquid injection (DLI) at a flow rate of 1100 mg / min using a He carrier gas flow of 900 sccm, and a 270 Watt 13.56 MHz plasma was applied at a chamber pressure of 7.5 Torr, with a showerhead / heated pedestal spacing of 380 mils, a pedestal temperature of 390° C., and an O flow rate of 8 sccm. Various properties of the as-deposited films, such as dielectric constant (k), elastic modulus, hardness, and density of various functional groups as determined by infrared spectroscopy, were obtained as described above and are provided in Table 1.

[0057] Example 12: Deposition of dense, iso-propyl-methyl-ethoxysilane (IPMEOS)-based films Dense, IPMEOS-based films were deposited using the following process conditions for a 300 mm process: IPMEOS precursor was delivered to the reaction chamber via direct liquid injection (DLI) at a flow rate of 1100 mg / min using a He carrier gas flow of 1200 sccm, and a 270 Watt 13.56 MHz plasma was applied at a chamber pressure of 7.5 Torr, with a showerhead / heated pedestal spacing of 380 mils, a pedestal temperature of 390° C., and an O flow rate of 24 sccm. Various properties of the as-deposited films, such as dielectric constant (k), elastic modulus, hardness, density of various functional groups as determined by infrared spectroscopy, and atomic composition by XPS, were obtained as described above and are provided in Tables 2 and 3.

[0058] Example 13: Deposition of dense, UV-cured isopropyl-methyl-ethoxysilane (IPMEOS)-based films Dense, IPMEOS-based films were deposited using the following process conditions for a 300 mm process: IPMEOS precursor was delivered to the reaction chamber via direct liquid injection (DLI) at a flow rate of 1100 mg / min using a He carrier gas flow of 1200 sccm, and a 270 Watt, 13.56 MHz plasma was applied at a chamber pressure of 7.5 Torr, with a showerhead / heated pedestal spacing of 380 mils, a pedestal temperature of 390° C., and an O flow rate of 24 sccm. To improve the mechanical properties of the as-deposited films, the films were then thermally treated using a Producer® Nanocure TM The films were UV cured in a chamber at a base temperature of 400° C. The length of the UV curing process was adjusted to maximize the mechanical properties of the films while having little to no effect on the dielectric constant of the films. Various properties of the UV cured films, such as dielectric constant (k), elastic modulus, hardness, density of various functional groups as determined by infrared spectroscopy, and atomic weight percent of carbon (%C), were obtained as described above and are provided in Table 3.

[0059] Table 1. Processing conditions for selective membranes with a dielectric constant of 3.2, adjusted to obtain a high elastic modulus. [Table 3]

[0060] Table 2. Processing conditions for selective membrane with dielectric constant of 3.1, adjusted to obtain high elastic modulus [Table 4]

[0061] Table 3. Comparative film properties of as-deposited k=3.1 films and UV-cured k=3.1 films deposited using iso-propyl-methyl-ethoxysilane (IPMEOS). [Table 5]

[0062] Table 1 shows comparative film properties for k=3.2 films deposited using dimethyl-diisopropoxysilane (DMDIPOS), iso-propyl-methyl-ethoxysilane (IPMEOS) and dimethyl-dimethoxysilane (DMDMOS). Table 2 shows comparative film properties for k=3.1 films deposited using DMDIPOS, IPMEOS, diethoxy-dimethylsilane (DEMS®) and DMDMOS. Processing conditions for all films in Tables 1 and 2 were adjusted to achieve high modulus. Infrared spectra of the four films in Table 2 are shown in FIG. 2. These spectra were used to determine the Si-Me (or Si(CH3)) content in each film as previously described. x The relative density of Si(CH3) groups and the relative density of SiCH2Si groups were calculated. Similarly, the infrared spectra of the films in Table 1 were used to calculate the relative density of Si(CH3) groups in each of the films described above. x The relative densities of the SiCH2Si group and the SiCH2Si group were calculated.

[0063] As summarized in Table 1, films deposited using DMDIPOS and IPMEOS have unexpectedly high modulus and hardness relative to DMDMOS-based films, with all films having a measured dielectric constant of 3.2. Compared to DMDMOS-based films, DMDIPOS and IPMEOS-based films have significantly higher mechanical properties and lower Si(CH3) x A similar trend is observed in Table 2, where films deposited using DMDIPOS and IPMEOS have unexpectedly higher modulus and hardness versus DEMS and DMDMOS based films. Compared to DEMS and DMDMOS based films, DMDIPOS and IPMEOS based films have significantly higher mechanical properties and lower Si(CH3) x It has density.

[0064] FIG. 5 shows the relative hardness versus Si(CH3) for the films in Table 2. x The data shows a plot of the density of the Si(CH3) xThe results show that the hardness of the films increases as the density of the silicon methyl decreases. The trend of increasing mechanical strength with decreasing silicon methyl density is consistent with behavior previously reported in the literature. However, it is unexpected that films deposited from IPMEOS, a monoalkoxysilane compound of formula (1), show higher mechanical strength than films deposited from the dialkoxysilane compound DEMS®, since DEMS®-based films are well known for their high mechanical strength. Similarly, it is unexpected that DMDIPOS, a dialkoxysilane compound of formula (2), shows such extremely high mechanical properties relative to films deposited from DMDMOS, since these two precursors are identical except for the alkoxy group. It is also unexpected that DMDIPOS-based films show the highest mechanical strength of this series of films.

[0065] Prior art silicon-containing structure-forming precursors, such as DEMS®, are polymerized after excitation in the reaction chamber to form structures with -O- bonds in the polymer backbone (e.g. -Si-O-Si- or Si-OC-), whereas monoalkoxysilane compounds, such as IPMEOS molecules, having the structure given in formula (1), are believed to polymerize to form structures in which a high percentage of the -O- bridges in the backbone are replaced with -CH2-methylene or -CH2CH2-ethylene bridges. In films deposited using prior art precursors, such as DEMS® and DMDMOS, in which carbon is present mainly in the form of terminal Si-Me groups, there is a relationship between %Si-Me (directly related to %C) and mechanical strength, see for example the model work shown in Figure 1. Here, the replacement of the bridging Si-O-Si groups with two terminal Si-Me groups reduces the mechanical properties due to the collapse of the network structure. In the case of monoalkoxysilane compounds having formula (1), it is believed that the precursor structure is broken down during deposition of the film to form SiCH2Si or SiCH2CH2Si bridging groups. In this way, carbon in the form of bridging groups can be incorporated so that the network structure is not disrupted by the increase in carbon content in the film from the standpoint of mechanical strength. Without being bound by theory, this property adds carbon to the film to make it more resilient to carbon depletion of dense films due to processes such as etching the film, plasma ashing of photoresist, and NH3 plasma treatment of copper surfaces. Carbon depletion in dense low-k films can cause an increase in the effective dielectric constant of the film, problems with etching the film, and bowing of features during wet cleaning steps, and / or integration problems when depositing copper diffusion barriers. Although deposition of prior art structure formers such as MESCP (1-methyl-1-ethoxy-1-silacyclopentane) can deposit low-k films with very high densities of cross-linked SiCH2Si and / or SiCH2CH2Si groups, these films also have very high Si-Me densities and total carbon contents that ultimately limit the highest elastic modulus that can be achieved with this type of prior art low-k precursor.For example, as taught in U.S. Pat. No. 9,922,818, when optimized for high mechanical properties, the elastic modulus of MESCP-based films approaches that of DEMS®-based films at the same value of dielectric constant.

[0066] The process conditions for the deposition of dense low-k films deposited in a 300 mm PECVD reactor using DMDIPOS, IPMEOS, DEMS®, and DMDMOS as low-k precursors are given in Table 2. The process conditions for each of these depositions were adjusted to obtain a high modulus with a dielectric constant of 3.1. The infrared spectra of the dense low-k films in Table 1 are shown in Figure 2. The Si(CH3) in each film x The relative densities of the SiCH2Si and SiCH2Si groups were calculated from their infrared spectra, as previously described.

[0067] A series of depositions of dense low-k dielectric films were deposited using either DMDIPOS or DMDMOS as the low-k precursor in a 300 mm PECVD reactor under various process conditions of plasma power from 230 to 525 watts, chamber pressure from 6.25 to 7.50 Torr, substrate temperature from 350 to 400°C, O2 gas flow from 8 to 125 sccm, He carrier gas flow from 925 to 1500 sccm, precursor liquid flow from 0.7 to 3.3 g / min, and electrode spacing of 0.380 inches. Elastic modulus was measured by nanoindentation as described herein. Figure 3 shows the relationship between the elastic modulus of dense, DMDIPOS and DMDMOS films with different dielectric constants. As Figure 3 shows, the prior art or DMDMOS low-k films have a lower elastic modulus at the same value of dielectric constant than DMDIPOS-based films as the dielectric constant increases from about 2.9 to about 3.2. This illustrates one of the key advantages of using the dialkoxysilane compounds of formula (2) described herein as DMDIPOS over the use of other prior art structure formers for depositing dense low-k dielectric films of similar dielectric constant values, demonstrating that films with higher elastic modulus can be deposited using the dialkoxysilane precursor DMDIPOS.

[0068] A series of dense low-k dielectric film depositions were performed using either DMDIPOS or DMDMOS as the low-k precursor in a 300 mm PECVD reactor under various process conditions: plasma power from 230 to 525 watts, chamber pressure from 6.25 to 7.50 Torr, substrate temperature from 350 to 400 °C, O2 gas flow from 8 to 125 sccm, He carrier gas flow from 925 to 1500 sccm, precursor liquid flow from 0.7 to 3.3 g / min, and electrode spacing of 0.380 inches. Si(CH3) x The density of the Si(CH3) group was calculated from the infrared spectrum for each film as described herein. Figure 4 shows the Si(CH3) group density of DMDIPOS and DMDMOS films with different dielectric constants and high density. xAs FIG. 4 shows, the prior art or DMDMOS low-k films have a higher density of Si(CH3) group than the DMDIPOS-based films at the same value of dielectric constant as the dielectric constant increases from about 2.9 to about 3.2. x This illustrates one of the key advantages of using the dialkoxysilane compounds of formula (2) described herein as DMDIPOS over the use of other prior art structure formers for depositing dense low-k dielectric films of similar dielectric constant values, with the dialkoxysilane precursor DMDIPOS being able to deposit the lower density Si(CH3) x This shows that it is possible to deposit a film having a lower density Si(CH3) group. x The group results in denser low-k films with increased mechanical properties since the network structure is less prone to collapse.

[0069] A series of dense low-k dielectric film depositions were deposited using either IPMEOS or DEMS® as the low-k precursor in a 300 mm PECVD reactor under various process conditions of plasma power from 170 to 550 watts, chamber pressure from 7.0 to 10.0 Torr, substrate temperature from 345 to 390°C, O2 gas flow from 0 to 40 sccm, He carrier gas flow from 600 to 2250 sccm, precursor liquid flow from 1.1 to 2.5 g / min, and electrode spacing of 0.380 inches. The density of the SiCH2Si group was calculated from the infrared spectrum for each film as described herein. Figure 6 shows the relationship between the density of the SiCH2Si group for dense, IPMEOS and DEMS® films with different dielectric constants. As shown in FIG. 6, the prior art or DEMS® low-k films have a lower density of SiCH2Si groups at the same value of dielectric constant versus IPMEOS-based films when the dielectric constant increases from about 2.9 to about 3.2. This illustrates one of the key advantages of using the monoalkoxysilane compound of formula (1) described herein as IPMEOS over the use of other prior art structure formers for depositing dense low-k dielectric films of similar value of dielectric constant, where the monoalkoxysilane precursor IPMEOS can be used to deposit films with a higher density of SiCH2Si groups. In this way, carbon in the form of bridging groups can be incorporated so that the network structure is not collapsed by the increase in carbon content in the film from the standpoint of mechanical strength. Without being bound by theory, this property adds carbon to the film to make it more resilient to carbon depletion of dense films due to processes such as etching of the film, plasma ashing of photoresist, and NH3 plasma treatment of copper surfaces.

[0070] DEMS®-based films are well known for their high mechanical strength, so it was unexpected that films deposited from IPMEOS, a monoalkoxysilane compound of formula (1), exhibited higher mechanical strength than films deposited from the well-known commercially available dialkoxysilane compound DEMS®. To illustrate, for dense low-k films (assuming similar deposition conditions), it can be seen that as the number of silicon-alkoxy groups (e.g., Si-OCH3, Si-OCH2CH3, etc.) in the low-k precursor increases and the number of silicon-carbon bonds (e.g., Si-CH3, Si-CH2CH3, etc.) in the precursor decreases, the dielectric constant and mechanical properties of the as-deposited films improve and the carbon content of the films decreases. Thus, films deposited from precursors containing four silicon-alkoxy groups and no silicon-carbon bonds per silicon atom in the precursor (e.g., TEOS) have higher dielectric constants, higher mechanical properties, and less carbon than films deposited from precursors containing three silicon-alkoxy groups per silicon and no more than one silicon-carbon bond per silicon (e.g., triethoxysilane or TES, and methyl-triethoxysilane or MTES); similarly, films deposited from precursors containing three silicon-alkoxy groups per silicon and no more than one silicon-carbon bond per silicon have higher dielectric constants, higher mechanical properties, and less carbon than films deposited from precursors containing two silicon-alkoxy groups per silicon and no more than one silicon-carbon bond per silicon. Compared to films deposited from precursors containing one silicon-alkoxy group and one or two silicon-carbon bonds (e.g. DEMS® and DMDMOS), films deposited from precursors containing two silicon-alkoxy groups and one or two silicon-carbon bonds per silicon have higher dielectric constants, higher mechanical properties, and less carbon; similarly, films deposited from precursors containing two silicon-alkoxy groups and one or two silicon-carbon bonds per silicon have higher elastic modulus compared to films deposited from precursors containing only one silicon-alkoxy group per silicon and three or fewer silicon-carbon bonds (e.g. diethyl-methyl-iso-propoxysilane and trimethylsilane). Indeed, in U.S. Pat. No. 8,137,764, this concept is utilized to improve the mechanical properties of dense low-k films by depositing the films using a controlled mixture of two different precursors during the deposition process.One precursor (hardening additive) is selected to improve the mechanical properties of the film and contains 3-4 silicon oxygen bonds per silicon atom and no silicon-carbon bonds, e.g. TEOS and triethoxysilane (TES). The second precursor, the low-k precursor, contains one or more silicon-carbon bonds, e.g. DEMS® or DMDMOS. A representative example is the deposition of a low-k film from a blend of TES (50%) and DEMS® (50%). The resulting film with k=3.17 deposited from a blend of TES and DEMS® had a higher hardness (1.76 GPa) than the film deposited from DEMS® alone (1.58 GPa) at the same value of the dielectric constant. The higher modulus of the low-k film deposited from a blend of TES and DEMS® is due to the higher oxygen content and possibly lower carbon content of this film compared to the film deposited from DEMS® alone. The increased oxygen content and decreased carbon content can lead to better three-dimensional network connectivity and thus improved mechanical properties. Thus, it was unexpected that films deposited from IPMEOS, a monoalkoxysilane compound of formula (1), exhibited higher mechanical strength than films deposited from the dialkoxysilane compound DEMS®, especially since DEMS®-based films are well known for their high mechanical strength.

[0071] A comparison of the films deposited from DMDIPOS and IPMEOS in Tables 1 and 2 is also instructive. The DMDIPOS-based films correspond to films deposited from dialkoxysilane compounds corresponding to formula (2), while the IPMEOS-based films correspond to films deposited from monoalkoxysilane compounds corresponding to formula (1). In both Tables 1 and 2, the DMDIPOS-based films exhibit higher mechanical properties, lower Si(CH3) xThus, in these examples, films deposited from dialkoxysilane compounds corresponding to formula (2) have higher mechanical properties, lower Si(CH3)2Si2O3 density, and lower SiCH2Si2O3 density, as compared to films deposited from monoalkoxysilane-based compounds corresponding to formula (1). x density, and a lower SiCH2Si density.

[0072] The data in Table 2 show that IPMEOS-based films, films deposited from a monoalkoxysilane compound corresponding to formula (1), have significantly higher mechanical properties than films deposited from the dialkoxysilane compound DEMS®, which was unexpected since DEMS®-based films are known for their high mechanical strength.

[0073] The data in Tables 1 and 2 show that IPMEOS-based films have the highest carbon content and highest SiCH2Si density compared to films deposited from three other dialkoxysilane compounds, DMDIPOS, DEMS®, and DMDMOS. Therefore, it is expected that films deposited from IPMEOS have a higher resistance to PID compared to films deposited from DMDIPOS, DEMS®, and DMDMOS. That is, for the same value of dielectric constant, it is expected that films deposited from monoalkoxysilane compounds corresponding to formula (1) have a higher carbon content and a higher SiCH2Si density compared to films deposited from dialkoxysilane compounds corresponding to formula (2). Therefore, for the same value of dielectric constant, it is expected that films deposited from monoalkoxysilane compounds corresponding to formula (1) have a higher resistance to PID compared to films deposited from dialkoxysilane compounds corresponding to formula (2). Films deposited from monoalkoxysilane compounds corresponding to formula (1) also exhibit unexpectedly enhanced mechanical properties compared to films deposited from industry standard dialkoxysilane low-k precursors, such as DEMS® and DMDMOS.

[0074] It is observed that the mechanical strength of the DMDIPOS-based films in Table 1 is significantly higher than that of the DMDMOS-based films in Table 1. Furthermore, the DMDIPOS-based films in Table 1 have a lower Si(CH3) x Similarly, the mechanical strength of the DMDIPOS-based films in Table 2 is significantly higher than that of the DMDMOS-based films in Table 2. Furthermore, the DMDIPOS-based films in Table 2 have a lower Si(CH3) x Has density.

[0075] Dimethyl-di-alkoxysilane-based DMDIPOS and DMDMOS precursors are identical except for the alkoxy group (in DMDIPOS, the alkoxy group is iso-propoxy (branched alkoxy group) and in DMDMOS, the alkoxy group is methoxy), so there is no significant difference in mechanical strength and Si(CH3) between DMDIPOS-based and DMDMOS-based films. x The difference in density was unexpected. The prior art does not consider the effect of precursor molecules with different alkoxy groups but otherwise identical on the properties of films deposited from these precursors. In the above example, films deposited from the branched isopropoxy derivative (DMDIPOS) had significantly higher mechanical properties and lower Si(CH3) solubility properties compared to films deposited from the unbranched methoxy derivative (DMDMOS). x It is clear that the granules have a density of 100%. Without being bound by theory, the granules are represented by the formula (2) in the present invention: (2) R 4 R 5 Si(OR 6 )2 The dialkoxysilane compound of the present invention is a linear, branched or cyclic C3-C alkoxy group in which the R group in the alkoxy group provides a more stable radical than the methyl, e.g., Me3SiOMe or Me3SiOEt, disclosed in the prior art (Bayer, C. et al., "Overall Kinetics of SiOx Remote-PECVD using Different Organosilicon Monomers", pp. 116-119, Surf. Coat. Technol., 874, (1999)). 10 When the alkyl group R is selected from the group consisting of alkyl, preferably propyl, iso-propyl, butyl, sec-butyl, iso-butyl, or tert-butyl, it can provide stable radicals, such as (CH3)2CH· and (CH3)3C·, during plasma enhanced chemical vapor deposition. A higher density of stable radicals, such as (CH3)2CH· and (CH3)3C·, in the plasma increases the possibility of reaction with one or both of the terminal silicon methyl groups in the DMDIPOS. This reduces the density of terminal silicon methyl groups in the film, resulting in a low-k film with higher mechanical properties. A higher density of stable radicals ... dialkoxysilane compound of formula (2). 5 It will be appreciated that this can be achieved when is selected from branched or cyclic alkyl, such as isopropyl, sec-butyl, t-butyl or cyclohexyl.

[0076] All properties described so far correspond to as-deposited films without post-deposition treatment such as UV curing, however, significantly higher mechanical properties can be obtained by UV curing films deposited from monoalkoxysilane compounds of formula (1) or dialkoxysilane compounds of formula (2). For illustration, the data in Table 3 compares the film properties of a deposited and UV cured IPMEOS-based low-k film with k=3.1. The IPMEOS-based low-k film with k=3.1 is the same film described in Table 2. After UV curing, the mechanical properties of the film increase by approximately 14%, resulting in a film with a dielectric constant of 3.1 and an elastic modulus of 27 GPa, which is very high for a low-k film with a dielectric constant of 3.1. The UV curing process reduces the carbon content of the film (approximately -4%) and the Si(CH3) x The UV curing process reduces both the SiCH2Si density (about -28%) and the SiCH2Si density (about +20%). Because the UV curing process may introduce some small amount of porosity and reduce the total carbon content of the film, it was unexpected that the UV cured films exhibited lower resistance to PID compared to the corresponding as-deposited films.

[0077] In comparison to commercially available industry standard dialkoxysilane low-k precursors, such as DEMS or DMDMOS, films deposited from monoalkoxysilane compounds corresponding to formula (1), such as IPMEOS-based films, and films deposited from dialkoxysilane compounds corresponding to formula (2), such as DMDIPOS-based films, exhibit unexpectedly high mechanical properties and lower Si(CH3) x Therefore, both are suitable for applications requiring low-k films with higher mechanical properties than DEMS- or DMDMOS-based films.

[0078] DMDIPOS-based films have higher mechanical properties compared to IPMEOS-based films, but IPMEOS-based films also have higher carbon content, higher Si(CH3) content, and higher Si(CH3) content compared to DMDIPOS-based films with the same k value. xIPMEOS-based films have a higher SiCH2Si density and a higher SiCH2Si density. Therefore, it is expected that IPMEOS-based films will exhibit a higher resistance to PID compared to DMDIPOS-based films. Furthermore, IPMEOS-based films have the highest SiCH2Si density in Tables 1 and 2. Furthermore, IPMEOS-based films have the highest carbon content in Table 2. Therefore, it is expected that IPMEOS-based films will exhibit a higher resistance to PID compared to films deposited from DMDIPOS, DEMS, or DMDMOS at the same value of dielectric constant. That is, for the same value of dielectric constant, films deposited using the monoalkoxysilane compound of formula (1) will have a higher carbon content, a higher Si(CH3)Si content, and a higher Si(CH3)Si content compared to films deposited using the dialkoxysilane compound of formula (2). x It is expected that the monoalkoxysilane compound of formula (1) has a higher density, a higher SiCH2Si density, and a higher resistance to PID. Therefore, the monoalkoxysilane compound of formula (1) may be more suitable for applications requiring both high mechanical strength and strong resistance to PID.

[0079] It will be appreciated that the advantages of the dense low-k films deposited using the available monoalkoxysilane compounds of formula (1) or dialkoxysilane compounds of formula (2) are not limited to dense low-k films, but can be readily extended to porous low-k deposition processes. The present invention can be embodied in the following manner. (Appendix 1) 1. A method for producing dense organosilica films having improved mechanical properties, comprising: Providing a substrate in a reaction chamber; Formulas (I) and (2): (1)HR 1 R 2 SiOR 3 (In the formula, R 1 is methyl, and R 2 Branched or cyclic C 3 ~C 10 alkyl, preferably iso-propyl or tert-butyl; R3 is linear, branched or cyclic C 1 ~C 10 alkyl, preferably selected from methyl, ethyl, propyl, iso-propyl, butyl, sec-butyl, iso-butyl, tert-butyl or cyclohexyl (2)R 4 R 5 Si(OR 6 ) 2 (In the formula, R 4 is hydrogen or methyl, R 5 is linear, branched or cyclic C 1 ~C 10 alkyl, preferably iso-propyl or tert-butyl; R 6 is linear, branched or cyclic C 3 ~C 10 alkyl, preferably selected from iso-propyl, sec-butyl, iso-butyl, cyclohexyl or tert-butyl introducing into the reaction chamber a gaseous composition comprising at least one monoalkoxysilane or dialkoxysilane having a structure given in applying energy to the gaseous composition comprising a monoalkoxysilane or a dialkoxysilane in the reaction chamber to induce a reaction of the gaseous composition comprising a monoalkoxysilane or a dialkoxysilane to deposit an organosilicon film on the substrate. wherein the organosilica film has a dielectric constant of about 2.80 to about 3.30 and an elastic modulus of about 7 to about 30 GPa. (Appendix 2) 2. The method of claim 1, wherein the gaseous composition comprising at least one monoalkoxysilane or dialkoxysilane does not contain a curing additive. (Appendix 3) 2. The method of claim 1, wherein the monoalkoxysilane or dialkoxysilane of formula (1) or (2) is substantially free of one or more impurities selected from the group consisting of halides, water, metals, and combinations thereof. (Appendix 4) 2. The method of claim 1, which is a chemical vapor deposition method. (Appendix 5) 2. The method of claim 1, which is a plasma-enhanced chemical vapor deposition method. (Appendix 6) The gaseous composition comprising at least one monoalkoxysilane or dialkoxysilane is 2 、N 2 O, NO, NO 2 , CO 2 , water, H 2 O 2 2. The method of claim 1, further comprising at least one oxidant selected from the group consisting of ozone and combinations thereof. (Appendix 7) 2. The method of claim 1, wherein the gaseous composition comprising at least one monoalkoxysilane or dialkoxysilane does not contain an oxidizing agent. (Appendix 8) In the applying step, the reaction chamber is 2 , Kr, Xe, CO 2 and CO. (Appendix 9) 2. The method of claim 1, wherein the organosilica film has a refractive index (RI) of about 1.3 to about 1.6 at 632 nm, and about 10 at % to about 30 at % carbon as measured by XPS. (Appendix 10) 2. The method of claim 1, wherein the organosilica film is deposited at a rate of about 5 nm / min to about 700 nm / min. (Appendix 11) The organic silica film is formed by mixing about 10 to about 30 SiCH 2 Si / SiO x ×10 4 The method of claim 8, having an IR ratio of (Appendix 12) The monoalkoxysilane or dialkoxysilane in the gaseous composition may be iso-propyl-methyl-methoxysilane, isopropyl-methyl-ethoxysilane, n-butyl-methyl-iso-propoxysilane, iso-butyl-methyl-iso-propoxysilane, isopropyl-methyl-isopropoxysilane, sec-butylmethylmethoxysilane, sec-butylmethylethoxysilane, sec-butylmethyl-iso-propoxysilane, t-butyl-methyl-methoxysilane, t-butyl-methyl-ethoxysilane, t-butyl-methyl-isopropoxysilane, cyclohexyl-methyl-methoxysilane, cyclopentyl-methyl- 2. The method of claim 1, comprising one or more precursors selected from the group consisting of cyclohexyl-methoxysilane, cyclopentyl-methyl-iso-propoxysilane, cyclohexyl-methyl-ethoxysilane, cyclohexyl-iso-propoxymethylsilane, di-iso-propoxy-dimethylsilane, di-isopropoxy-methylsilane, di-t-butoxy-dimethylsilane, di-t-butoxy-methylsilane, dicyclohexoxy-dimethylsilane, dicyclohexoxy-methylsilane, di-sec-butoxy-dimethylsilane, di-sec-butoxy-methylsilane, dicyclopentoxydimethylsilane, and dicyclopentoxymethylsilane. (Appendix 13) 2. The method of claim 1, wherein the monoalkoxysilane or dialkoxysilane in the gaseous composition comprises one or more precursors selected from the group consisting of iso-propyl-methyl-ethoxysilane, iso-methyl-propyl-iso-propoxysilane, di-iso-propoxy-dimethylsilane, di-t-butoxy-dimethylsilane, di-sec-butoxy-dimethylsilane, dicyclohexoxy-dimethylsilane, dicyclohexoxymethylsilane, dicyclopentoxy-dimethylsilane, and dicyclopentoxymethylsilane. (Appendix 14) Formulas (I) and (2): (1)HR 1 R 2 SiOR 3 (In the formula, R 1 is methyl, and R 2 Branched or cyclic C 3 ~C 10 alkyl, preferably iso-propyl or tert-butyl; R 3 is linear, branched or cyclic C 1 ~C 10 alkyl, preferably selected from methyl, ethyl, propyl, iso-propyl, butyl, sec-butyl, iso-butyl, tert-butyl or cyclohexyl (2)R 4 R 5 Si(OR 6 ) 2 (In the formula, R 4 is hydrogen or methyl, R 5 is linear, branched or cyclic C 1 ~C 10 alkyl, preferably iso-propyl or tert-butyl; R 6 is linear, branched or cyclic C 3 ~C 10 alkyl, preferably selected from iso-propyl, sec-butyl, iso-butyl, cyclohexyl or tert-butyl 1. A gaseous composition comprising at least one monoalkoxysilane or dialkoxysilane having a structure provided in claim 1, wherein the gaseous composition is substantially free of one or more impurities selected from the group consisting of halides, water, metals, and combinations thereof. (Appendix 15) The at least one monoalkoxysilane or dialkoxysilane may be selected from the group consisting of isopropyl-methyl-methoxysilane, isopropyl-methyl-ethoxysilane, n-butyl-methyl-iso-propoxysilane, isobutyl-methyl-iso-propoxysilane, isopropyl-methyl-isopropoxysilane, sec-butylmethylmethoxysilane, sec-butylmethylethoxysilane, sec-butylmethyl-iso-propoxysilane, t-butyl-methyl-methoxysilane, t-butyl-methyl-ethoxysilane, t-butyl-methyl-isopropoxysilane, cyclohexyl-methyl-methoxysilane, cyclopentyl 15. The gaseous composition of claim 14, wherein the compound is selected from the group consisting of cyclohexyl-2-methyl-methoxysilane, cyclopentyl-methyl-iso-propoxysilane, cyclohexyl-methyl-ethoxysilane, cyclohexyl-iso-propoxymethylsilane, di-iso-propoxy-dimethylsilane, di-isopropoxy-methylsilane, di-t-butoxy-dimethylsilane, di-t-butoxy-methylsilane, dicyclohexoxy-dimethylsilane, dicyclohexoxy-methylsilane, di-sec-butoxy-dimethylsilane, di-sec-butoxy-methylsilane, dicyclopentoxydimethylsilane, and dicyclopentoxymethylsilane. (Appendix 16) 15. The gaseous composition of claim 14, wherein the at least one monoalkoxysilane or dialkoxysilane is selected from the group consisting of iso-propyl-methyl-ethoxysilane, iso-methyl-propyl-iso-propoxysilane, di-iso-propoxy-dimethylsilane, di-t-butoxy-dimethylsilane, di-sec-butoxy-dimethylsilane, dicyclohexoxy-dimethylsilane, dicyclohexoxymethylsilane, dicyclopentoxy-dimethylsilane, and dicyclopentoxymethylsilane. (Appendix 17) 15. The gaseous composition of claim 14 having less than 5 ppm of a metal selected from the group consisting of Li, Na, K, Mg, Ca, Al, Fe, Fe, Ni, and Cr, as measured by ICP-MS. (Appendix 18) 15. The gaseous composition of claim 14 having less than 0.1 ppm of a metal selected from the group consisting of Li, Na, K, Mg, Ca, Al, Fe, Fe, Ni, and Cr, as measured by ICP-MS. (Appendix 19) 15. The gaseous composition of claim 14 having less than 50 ppm of halides. (Appendix 20) 20. The composition of claim 19, wherein the halide is chloride ion and, if present, is present at a concentration of 10 ppm or less as measured by IC. (Appendix 21) 20. The composition of claim 19, wherein the halide is chloride ion and, if present, is present at a concentration of 5 ppm or less as measured by IC. (Appendix 22) 2. A gaseous composition for vapor deposition of silicon-containing films comprising at least one monoalkoxysilane or dialkoxysilane selected from the group consisting of iso-butyl-methyl-iso-propoxysilane, isopropyl-methyl-isopropoxysilane, sec-butylmethylethoxysilane, sec-butylmethyl-iso-propoxysilane, t-butyl-methyl-isopropoxysilane, cyclohexylethoxymethylsilane, cyclohexylisopropoxymethylsilane, di-iso-propoxy-dimethylsilane, di-t-butoxy-dimethylsilane, di-sec-butoxy-dimethylsilane, dicyclohexoxy-dimethylsilane, dicyclohexoxymethylsilane, dicyclopentoxy-dimethylsilane, and dicyclopentoxymethylsilane.

Claims

1. 1. A method for producing dense organosilica films having improved mechanical properties, comprising: providing a substrate in a reaction chamber; Formulas (1) and (2): (1) HR 1 R 2 SiOR 3 (In the formula, R 1 is methyl, R 2 is a branched or cyclic C 3 ~C 10 alkyl; R 3 is a straight chain, branched chain or cyclic C 1 ~C 10 alkyl) (2)R 4 R 5 Si(OR 6 ) 2 (In the formula, R 4 is hydrogen or methyl; R 5 is a straight chain, branched chain or cyclic C 1 ~C 10 alkyl; R 6 is a straight chain, branched chain or cyclic C 3 ~C 10 alkyl) introducing into the reaction chamber a gaseous composition comprising at least one monoalkoxysilane or dialkoxysilane having a structure given in applying energy to the gaseous composition comprising a monoalkoxysilane or a dialkoxysilane in the reaction chamber to induce a reaction of the gaseous composition comprising a monoalkoxysilane or a dialkoxysilane to deposit an organosilica film on the substrate. wherein the organosilica film has a dielectric constant of 2.80-3.30 and an elastic modulus of 7-30 GPa, and wherein in the applying step, the reaction chamber contains at least one gas selected from the group consisting of He, Ar, N2, Kr, Xe, CO2 and CO, and the organosilica film has an IR ratio of SiCH2Si / SiOx x ×104 of 11-19.

2. 10. The method of claim 1, wherein the gaseous composition comprising at least one monoalkoxysilane or dialkoxysilane does not contain a curing additive.

3. 2. The method of claim 1, wherein the monoalkoxysilane or dialkoxysilane of formula (1) or (2) is substantially free of one or more impurities selected from the group consisting of halides, water, metals, and combinations thereof.

4. The method of claim 1 which is a chemical vapor deposition method.

5. The method of claim 1 , which is a plasma enhanced chemical vapor deposition method.

6. The gaseous composition comprising at least one monoalkoxysilane or dialkoxysilane is 2 , N 2 O, NO, NO 2 , CO 2 , water, H 2 O 2 10. The method of claim 1, further comprising at least one oxidant selected from the group consisting of ozone and combinations thereof.

7. 10. The method of claim 1, wherein the gaseous composition comprising at least one monoalkoxysilane or dialkoxysilane does not include an oxidizer.

8. 10. The method of claim 1, wherein the organosilica film has between 10 at% and 30 at% carbon as measured by XPS.

9. The method of claim 1 , wherein the organosilica film is deposited at a rate of from 5 nm / min to 700 nm / min.

10. The monoalkoxysilane or dialkoxysilane in the gaseous composition is selected from the group consisting of iso-propyl-methyl-methoxysilane, isopropyl-methyl-ethoxysilane, n-butyl-methyl-iso-propoxysilane, iso-butyl-methyl-iso-propoxysilane, isopropyl-methyl-isopropoxysilane, sec-butylmethylmethoxysilane, sec-butylmethylethoxysilane, sec-butylmethyl-iso-propoxysilane, t-butyl-methyl-methoxysilane, t-butyl-methyl-ethoxysilane, t-butyl-methyl-isopropoxysilane, cyclohexyl-methyl-methoxysilane, cyclopentyl-methyl- 2. The method of claim 1, comprising one or more precursors selected from the group consisting of cyclohexyl-methoxysilane, cyclopentyl-methyl-iso-propoxysilane, cyclohexyl-methyl-ethoxysilane, cyclohexyl-iso-propoxymethylsilane, di-iso-propoxy-dimethylsilane, di-isopropoxy-methylsilane, di-t-butoxy-dimethylsilane, di-t-butoxy-methylsilane, dicyclohexoxy-dimethylsilane, dicyclohexoxy-methylsilane, di-sec-butoxy-dimethylsilane, di-sec-butoxy-methylsilane, dicyclopentoxydimethylsilane, and dicyclopentoxymethylsilane.

11. 2. The method of claim 1, wherein the monoalkoxysilane or dialkoxysilane in the gaseous composition comprises one or more precursors selected from the group consisting of iso-propyl-methyl-ethoxysilane, iso-propyl-methyl-iso-propoxysilane, di-iso-propoxy-dimethylsilane, di-t-butoxy-dimethylsilane, di-sec-butoxy-dimethylsilane, dicyclohexoxy-dimethylsilane, dicyclohexoxymethylsilane, dicyclopentoxy-dimethylsilane, and dicyclopentoxymethylsilane.

12. Isopropyl-methyl-methoxysilane, isopropyl-methyl-ethoxysilane, n-butyl-methyl-isopropoxysilane, isobutyl-methyl-isopropoxysilane, isopropyl-methyl-isopropoxysilane, sec-butylmethylmethoxysilane, sec-butylmethylethoxysilane, sec-butylmethyl-isopropoxysilane, t-butyl-methyl-methoxysilane, t-butyl-methyl-ethoxysilane, t-butyl-methyl-isopropoxysilane, cyclohexyl-methyl-methoxysilane, cyclopentyl-methyl-methoxysilane, cyclopentyl-methyl-isopropoxysilane 1. A gaseous composition comprising at least one monoalkoxysilane or dialkoxysilane selected from the group consisting of cyclohexyl-2-methyl-1,3-dimethyl ...

13. 13. The gaseous composition of claim 12, wherein the at least one monoalkoxysilane or dialkoxysilane is selected from the group consisting of iso-propyl-methyl-ethoxysilane, iso-propyl-methyl-iso-propoxysilane, di-sec-butoxy-dimethylsilane, dicyclohexoxy-dimethylsilane, dicyclohexoxymethylsilane, dicyclopentoxy-dimethylsilane, and dicyclopentoxymethylsilane.

14. 13. The gaseous composition of claim 12 having less than 5 ppm of metals selected from the group consisting of Li, Na, K, Mg, Ca, Al, Fe, Fe, Ni, and Cr as measured by ICP-MS.

15. 13. The gaseous composition of claim 12 having less than 0.1 ppm of metals selected from the group consisting of Li, Na, K, Mg, Ca, Al, Fe, Fe, Ni, and Cr as measured by ICP-MS.

16. 13. The gaseous composition of claim 12 having less than 50 ppm halides.

17. 17. The composition of claim 16, wherein the halide is chloride ion and, if present, is present in a concentration of 10 ppm or less as measured by IC.

18. 17. The composition of claim 16, wherein the halide is chloride ion and, if present, is present in a concentration of 5 ppm or less as measured by IC.

19. 1. A gaseous composition for vapor phase deposition of silicon-containing films comprising at least one monoalkoxysilane or dialkoxysilane selected from the group consisting of iso-butyl-methyl-iso-propoxysilane, isopropyl-methyl-isopropoxysilane, sec-butylmethylethoxysilane, sec-butylmethyl-iso-propoxysilane, t-butyl-methyl-isopropoxysilane, cyclohexylethoxymethylsilane, cyclohexylisopropoxymethylsilane, di-sec-butoxy-dimethylsilane, dicyclohexoxy-dimethylsilane, dicyclohexoxymethylsilane, dicyclopentoxy-dimethylsilane, and dicyclopentoxymethylsilane.

Citation Information

Patent Citations

  • Method of forming low dielectric constant interlayer dielectric film

    JP2002256434A

  • Porous low dielectric constant composition, and methods for producing and using the same

    JP2006100833A

  • Porogen, porogenated precursor, and method for using the same to form porous organosilica glass film with low dielectric constant

    JP2009272632A

  • ORGANIC SILANE COMPOUND FOR FORMING Si-CONTAINING FILM BY PLASMA CVD AND METHOD FOR FORMING Si-CONTAINING FILM

    JP2010157689A

  • Alkyl-alkoxysilacyclic compound and method for depositing films using the same

    JP2016005001A